2012
DOI: 10.1007/s11356-012-1010-1
|View full text |Cite
|
Sign up to set email alerts
|

Relative bioavailability of tropical volcanic soil-bound chlordecone in laying hens (Gallus domesticus)

Abstract: The former use of chlordecone (CLD) in the French West Indies has resulted in long-term pollution of soils and of food chains. CLD may be transferred into eggs of hens reared outdoors, through polluted soil ingestion. Tropical volcanic soils display variable capacities of pollutant retention: CLD is less available and more persistent in andosol than in nitisol. The impact of soil type on CLD bioavailability to hens was tested through a relative bioavailability study. The deposition of CLD in egg yolk and in ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 27 publications
3
19
0
Order By: Relevance
“…Comparison between oil-fed and soil-fed animals groups was realized in order to assess exposure to spiked soil with OM in terms of exposure via the alimentary one. Similar methodology was previously used [19] [21] . The present study provides RBA estimates using a single dose comprised in a linearity-tested range of doses [17] .…”
Section: Methodsmentioning
confidence: 95%
“…Comparison between oil-fed and soil-fed animals groups was realized in order to assess exposure to spiked soil with OM in terms of exposure via the alimentary one. Similar methodology was previously used [19] [21] . The present study provides RBA estimates using a single dose comprised in a linearity-tested range of doses [17] .…”
Section: Methodsmentioning
confidence: 95%
“…Indeed involuntary soil ingestion represents a major 2 pesticide exposure pathway for outdoor reared animals (Fries et al, 1982) especially in the Antillean context (Jurjanz et al, 2017). Furthermore, it has recently been shown that CLDtransfers to animals are not limited by soil type or properties, as noticed in piglets (Bouveret et al, 2013, Delannoy et al, 2014a, lambs (Jurjanz et al, 2014), and laying hens-related studies (Fournier et al, 2012. Overall, for these domestic animal species, relative CLD bioavailability factors were not statistically different from 100% (Bouveret et al, 2013, Jurjanz et al, 2014.…”
Section: Introduction _________________________________________________mentioning
confidence: 90%
“…CLD-transfer to lambs [8], piglets [9] and laying hens [10] have been proven to not be limited by the type and properties of Antillean soils (nitisol or andosol). The specific efficiency of this transfer is related to the availability of this pesticide for outdoor reared animals.…”
Section: Introductionmentioning
confidence: 99%